2006
DOI: 10.1002/dev.20142
|View full text |Cite
|
Sign up to set email alerts
|

Nonnutritive sucking: One of the major determinants of filial love

Abstract: The present study investigated the rewarding effects of nonnutritive sucking on the development of a filial preference. Two experiments were conducted to test whether nonnutritive visceral and oral stimuli have reinforcing properties independent from each other or act in synergy. Lambs could interact freely with their dam but were deprived of suckling by covering the udder for the first 12 hr. In Experiment 1, suckling was prevented and replaced by human giving, in the presence of the mother, either a bottle o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 47 publications
0
5
0
1
Order By: Relevance
“…Using the same paradigm of suckling deprivation, it was shown that several aspects of the neonatal suckling activity could facilitate the development of a preference for the mother. Replacing suckling by repeated infusions of colostrum into the lamb’s stomach through a nasogastric canula triggers a preference for the mother (60, 61). The same behavioural outcome is obtained with infusions of a non‐nutritive liquid such as saline, although only when it is given in twice the volume required for colostrum.…”
Section: Development Of Attachment Behaviour: the First 3 Days After mentioning
confidence: 99%
“…Using the same paradigm of suckling deprivation, it was shown that several aspects of the neonatal suckling activity could facilitate the development of a preference for the mother. Replacing suckling by repeated infusions of colostrum into the lamb’s stomach through a nasogastric canula triggers a preference for the mother (60, 61). The same behavioural outcome is obtained with infusions of a non‐nutritive liquid such as saline, although only when it is given in twice the volume required for colostrum.…”
Section: Development Of Attachment Behaviour: the First 3 Days After mentioning
confidence: 99%
“…Through the cascade of neurophysiological events that are triggered during suckling, colostrum ingestion also shapes the behaviour of the neonate with biochemical and visceral mechanical stimulation. Recent studies have also demonstrated that non nutritive sucking facilitated early filial bonding [80].…”
Section: Getting Attached To the Mothermentioning
confidence: 99%
“…A 30-min social dominance trial began when all six birds were released into the experimental arena. We video recorded all interactions and noted the order in which birds fed from the food dish ( Boogert et al 2006 ; Val-Laillet et al 2006 ; David et al 2011 ), the number of aggressive interactions initiated by each bird, as well as all displacements between birds. From these latter observations we constructed a matrix of wins and losses and assigned a rank score based on wins minus losses, with lower numbers indicating higher social rank.…”
Section: Methodsmentioning
confidence: 99%